A Clinical Study and Short Term Outcome of the Patients Presented with Thyroiditis - Afrose, Rafia; Ahasan, H A M Najmul; Das, Aparna; Banik, Gobinda; Khan, Abed Hussain; Shazzad, Md. Nahiduzzamane; Siddique, Ashfaque Ahmed; Khan, Mohammad Ashik Imran; Chowdhury, Mostofa Kamal (Journal of Medicine, 2013)
Background: Thyroiditis-inflammation of thyroid gland includes a group of individual disorders having many different clinical presentations, aetiopathogenesis and histology. Sometimes they are overlapping on their presentations. Objectives: To see the clinical biochemical profile and to observe a short term outcome of the patients presented with different types of thyroiditis. Materials & methods: 50 cases with clinical suspicion of thyroiditis were randomly selected. Clinical history, Physical examination and serum T3, T4, TSH was done in every patient and FNAC of thyroid gland & TMab (Thyroid microsomal antibody) was estimated in some. They were followed up at three monthly intervals with the measurement of TSH. Results: Cases were subdivided in to 3 groups. Among them subacute thyroiditis were 19 (38%), 26 (52%) were Hashimotos thyroiditis and 5(10%) were silent thyroiditis. The subacute group presented with features of hyperthyroidism, negligible RAIU (radioactive iodine uptake) and FNAC ( Fine Needle Aspiration Cytology) showed granulomatous thyroiditis. During follow up (57%) became hypothyroid at 3 months, (26%) euthyroid and (15%) in thyrotoxic state. After 9 months (87%) was hypothyroid and (5.26%) thyrotoxic. At 12 months (94%) was euthyroid and one thyrotoxic. Hashimotos group presented in hypothyroid state, RAIU test were variable. FNAC showed lymphocytic infiltration in all patients. They were found 100% hypothyroid after 1 year. Silent Thyroiditis group were in hyperthyroid state with negligible RAIU. After 12 month (60%) became euthyroid and (40%) remain hypothyroid. Conclusion: Thyroiditis has both thyrotoxic and hypothyroid phase but they are self limiting. So before giving specific therapy, thyroiditis must be excluded. DOI: http://dx.doi.org/10.3329/jom.v14i1.14532 J MEDICINE 2013; 14 : 23-27